PENDAMPINGAN PENURUNAN STUNTING MELALUI GONG CETING DI DESA TIENG KEJAJAR WONOSOBO - Nurma Khusna Khanifa; Kurniawati Mutmainah; Ahmad Khoiri; Muhammad Radito Sanjaya; Sehan Ashari; Ziyad Faraihu Roihan (Jurnal Abdimas Bina Bangsa, 2022)
Stunting is a health problem that is a factor inhibiting human development globally. Based on the survey on the nutritional status of Indonesia in 2021, Wonosobo Regency ranks first in the prevalence of stunting at 28.1%, while based on the electronic Community-Based Nutrition Recording and Reporting for 2022 it is 19.23%. One of the efforts to prevent stunting in this service is Gong Ceting. Gong Ceting has a target of 14% nationally in 2024. The model developed in this service is the first counseling on the prevalence of Gong Ceting stunting. Second, prevention of stunting at 8000 HPK. The service was carried out in Tieng Kejajar Village, Wonosobo. The purpose of this activity is to increase public knowledge about stunting prevention. The results obtained from counseling through Gong Ceting carried out by the Community Service Team are strategic efforts to detect early disturbances to growth and health and realize Village priorities by mobilizing communities to live healthy lives. Meanwhile, to prevent stunting, the Service Team together with posyandu cadres conduct counseling starting from pregnant women to teenagers aged 19 years